PREVALENCIA DE PLACA BACTERIANA, CARIES DENTAL Y MALOCLUSIONES EN 300 ESCOLARES DE 6 A 14 AÑOS DE EDAD - Lahoud S., Víctor (2000)
The present research to consist ¡n evaluate the prevalence of bacterial plaque, caries and maloclussions in 300 pupil school, of 6 to 14 years old. The results show wath the 14.9% present a average of index of plaque 0-0.09 (good), 31.9% a index of plaque was of 1-1.9 (medium) and in the 53.3% average of index of plaque was 2-3 (bad). The index average CPO was 3.18 and the ceo 2.91 mean 6 tooth affected with index for each pupil school. The average of maloclussions clase I was the 2.0%, the normo oclussions of 14.3%, the class II division I was the 2.0% not to see acopopated form case class III true.